2013
DOI: 10.1051/0004-6361/201219901
|View full text |Cite
|
Sign up to set email alerts
|

The creation of photonic orbital angular momentum in electromagnetic waves propagating through turbulence

Abstract: Context.We have recently shown that the phenomenon known as "branch points" in AO are markers for photons carrying orbital angular momentum (OAM). In doing so, we have demonstrated that atmospheric turbulence creates well defined OAM states in beams propagating through it. Aims. In this paper, we extend our previous research to include any astrophysical turbulent assemblage of molecules or atoms (TAMA), demonstrating that these clouds, similar to Earth's atmosphere, also create photonic orbital angular momentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Table 3 shows the original results of the 2011 SOR observations from Sanchez et al (2013) by star name and observation time. The 2011 conversion efficiencies are provided along with the relative signal strengths as the number of standard deviations above the noise floor, N σ .…”
Section: Poam Estimation Through ηmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 3 shows the original results of the 2011 SOR observations from Sanchez et al (2013) by star name and observation time. The 2011 conversion efficiencies are provided along with the relative signal strengths as the number of standard deviations above the noise floor, N σ .…”
Section: Poam Estimation Through ηmentioning
confidence: 99%
“…Interestingly, both Silva et al (2011) andHarper (1992) studied HR 1577 for evidence of turbulence. However, they were looking at turbulence in the photospheres of G and K stars whereas Sanchez et al (2013) was looking for TAMA between the Earth and the candidate stars. The original analysis concluded that any POAM signal was below the noise floor of the detector.…”
Section: Hr 1577mentioning
confidence: 99%
See 3 more Smart Citations